Modern Joining Procedures in Automotive Industry - Zgonik, Miran; Polajnar, Ivan (Promet - Traffic&Transportation, 2012)
Besides standard joining procedures in automotive industrya n wnber of a ltema ti ve solutions are used, based on specific industrialneeds.This article briefly presents the basic conditions that mustbe met by the automobiles of new generation and states the reasonsfor an in-depth change in the concepts of construction andmaterials used as well as in the joining technology. The newconcepts in automotive indust1y are presented thatlzave provenacceptable and have been fully implemented.